2004
DOI: 10.1190/1.1707060
|View full text |Cite
|
Sign up to set email alerts
|

Crosswell electromagnetic and seismic imaging: An examination of coincident surveys at a steam flood project

Abstract: We studied crosswell electromagnetic and seismic images of three oil‐saturated intervals within a southern California heavy oil field undergoing steam flood. The crosswell survey is located in a portion of the field where one well is in a “cold spot,” resulting in differing steam propagation within the three units. Log analysis shows linear or second‐order polynomial relationships (with correlation coefficients greater than 0.7) between electrical conductivity and water saturation, porosity, and clay content; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Hoversten et al combined coincident high resolution crosswell seismic, electromagnetic surveys and well logs to monitor a CO 2 flood in Lost Hills, California. The presence of three distinct reservoir fluids made interpretation of individual surveys challenging.…”
Section: Challenges In Monitoring At the Basin Scalementioning
confidence: 99%
“…Hoversten et al combined coincident high resolution crosswell seismic, electromagnetic surveys and well logs to monitor a CO 2 flood in Lost Hills, California. The presence of three distinct reservoir fluids made interpretation of individual surveys challenging.…”
Section: Challenges In Monitoring At the Basin Scalementioning
confidence: 99%
“…This paper describes a model study to investigate the possibility of using steel casing as an electromagnetic (EM) source to detect and quantify oil-saturated formations and to estimate time-lapse variations of electrical resistivity due to fluid movement in an active hydrocarbon reservoir. Complementary experimental results in this area of research can be found in Kirkendall et al (1999), Hoversten et al (1995), and Bevc and Morrison (1991). In this work, we employ a numerical method to simulate cross-well and borehole-to-surface EM measurements in the presence of cased wells.…”
Section: Introductionmentioning
confidence: 98%
“…Wilt et al (1995Wilt et al ( , 1997 reported on the application of crosswell EM in steamflood monitoring. Hoversten et al (2004) introduced an examination of coincident surveys of crosswell electromagnetic and seismic imaging at a steam flood project and demonstrated the sensitivity of the two techniques to different reservoir parameters. In 1997, Shengli oil field in East China, in cooperation with the EMI Company, carried out a large scale pilot test of cross-hole EM measurement.…”
Section: Introductionmentioning
confidence: 99%